TECHNIQUES FOR IMPROVING ARABIC LANGUAGE LEARNING OUTCOMES OF TPA SANTRI AT THE DAARUL ABROR MOSQUE GUNUNGKIDUL - Khabibul Umam, Mustolikh; Fatikhin, Roro (STIT Pringsewu, 2024)
Abstract This research is based on several research objectives in the Gunungkidul area, namely 1) knowing learning techniques in improving Arabic learning outcomes, 2) knowing the supporting and inhibiting factors for learning empowerment in improving learning outcomes, 3) knowing the results achieved from techniques learning in improving Arabic language learning outcomes. Subjects used as targets for research include TPA leaders, Ustadz and Ustadzah, TPA students or students. The total number of subjects is 30 people. The author uses the documentation method as a method of observation, questionnaires, interviews. As for obtaining quantitative data, the author used descriptive methods. The results of this research are Learning Empowerment as follows: 1) the importance of learning in improving Arabic language learning outcomes for students, 2) efforts to encourage students to actively participate in learning activities in improving Arabic language learning outcomes, 3) the need for support from parents and the community in the form of materially and spiritually so that students are motivated to improve their Arabic learning outcomes. Supporting factors include: 1) the awareness of Ustadz and ustadzah in educating students, 2) the ability of Ustadz or ustadzah in caring for their students, 3) families educating and directing their children who are taught at TPA. Factors inhibiting activities include social friends, busy parents, TV shows, surrounding environment. Keywords: Technique, Learning, Arabic